Compatibility between entomopathogenic fungi and biorational insecticides in toxicity against Ronderosia bergi under laboratory conditions - Pelizza, Sebastian A. (2015)
Our aim was to evaluate the efficacy of combinations between two biorational insecticides (luphenuron, methoxyfenozide), a new synthetic chemical pesticide (rynaxypyr), and three entomopathogenic fungi strains (Beauveria bassianaLPSc 1067, LPSc1082), and Metarhizium anisopliae (LPSc 907) in the biocontrol of the pest grasshopper Ronderosia bergi (Stål) under laboratory conditions. The insecticides were tested at three concentrations: the average concentration recommended for application in the field (100%) and 50% and finally 25% of that level. The fungal strains used were adjusted to 1×108, 1×106, and 1×104conidia ml-1. The combinations of those insecticides with B. bassiana (LPSc 1067, LPSc 1082) and M. anisopliae (LPSc 907) caused higher mortality to R. bergi nymphs than any of the individual agents used alone. The three insecticides tested did not affect the isolates of the two species of entomopathogenic fungi employed. In conclusion, the use of these biorational insecticides in an IPM program aimed at control of the grasshopper R. bergicould be of value.